INFESTASI SOIL TRANMITTED HELMINTHS DAN PERILAKU HIGIENE PADA MURID KELAS I SEKOLAH DASAR DI PESISIR SUNGAI SIAK KECAMATAN RUMBAI KOTA PEKANBARU - Suci Aryanti; Suri Dwi Lesmana; Esy Maryanti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTSoil transmitted helminths (STH) infestation still become health problem in Indonesia. Specieses of STH which usually infested humans are Ascaris lumbricoides, Trichuris trichiura, Necator americanus and Ancylostoma duodenale. One of STH infestation factor is a bad hygiene. The aim of this research was to determine the relationship between infestation of STH with hygiene on elementary students grade I in pesisir Siak River Kecamatan Rumbai Pekanbaru. This research was cross sectional analitic study which was done in November 2014. For determine the relationship between infestation of STH with hygiene from 61 sampels, assessed with Chi square test to test alternatives Fisher. From research in laboratory 16 students (26.2%) are infested with soil transmitted helminths and from questionnaire 1 student (1.63%) has bad hygiene. From the analysis data there is no significant relationship between infestation of STH with hygiene (p value = 0,262).Key words: infestation of soil transmitted helminths, hygiene, pesisir Siak River